ASEAN evaluation instruments for Drug Abuse Prevention Education (DAPE) programs. (The Center, 1996)
Manuals for administration (students, teachers, parents) Purpose: This manual aims to develop, validate, and officially adapt proper evaluation instruments for the assessment of drug abuse prevention education programs of ASEAN member countries